Go digital: Enhancing the capacity of cultural sector SMEs through socialization of government procurement regulations - Probohudono, Agung Nur; Suhardjanto, Djoko; Bandi, Bandi; Winarna, Jaka (Universitas Muhammadiyah Magelang, 2025)
Cultural-based Small and Medium Enterprises (SMEs) are crucial for regional economic growth and cultural preservation. However, they often face challenges in adopting technology and participating in government's electronic procurement (e-procurement) of goods and services. This community engagement initiative aimed to address these issues by providing cultural sector SMEs in Surakarta with an understanding of the latest amendments to government procurement regulations. The activity also educated participants on the roles and functions of the online store and electronic catalog within the government procurement system. Our methodology included developing comprehensive socialization materials, creating practical training modules, and facilitating interactive sessions that combined socialization, consultation, and group discussions. The results demonstrated a significant improvement in the participants' comprehension of recent procurement regulations and the functions of the online store and electronic catalog. Participants also reported increased confidence in their ability to participate in government procurement processes. This activity successfully enhanced the digital literacy and technical readiness of cultural SMEs to engage with the government's e-procurement ecosystem. By doing so, it has opened new avenues for expanded market access and contributed to regional economic growth.